Hubungan Subjective Well Being Dengan Stress Kerja Perawat Di Massa Pandemi COVID-19 Di Instalasi Rawat Inap RSUD Depok - Devira Gite Pratiwi (2022)
In the Covid-19 pandemic, nurses can feel work stress, causing low subjective well-being. Subjective well being can also be assessed by the presence of cognitive and affective aspects. Work stress is an inability where a person feels depressed about what they are experiencing and can also cause more physical or psychological stress. This study aims to determine the relationship between subjective well-being and the work stress of nurses during the COVID-19 pandemic at the Depok Hospital Inpatient Installation. This research method uses descriptive analytic with cross sectional method. The sampling technique used was total sampling with a total of 60 respondents. Data analysis applied was chi-square test at 95% CI. The results of statistical tests showed that there was no significant relationship between age (p-value = 0.54), gender (p-value = 0.643), years of service (p-value = 0.809), marital status (p-value = 0.941 ), and education level (p-value = 0.466) with nurse work stress. In addition, the results also showed that there was a significant relationship between subjective well-being and the work stress of nurses during the COVID-19 pandemic at the Depok Hospital Inpatient Installation (p-value = 0.002). The recommendation of this research is that hospital management is expected to be able to evaluate the level of work stress with subjective well being for nurses during the covid-19 pandemic.